Bidirectional association between perioperative skeletal muscle and subcutaneous fat in colorectal cancer patients and their prognostic significance - Yan, Guanghong; Liu, Lizhu; Liu, Mengmei; Jiang, Xinyue; Chen, Ping; Li, Min; Ma, Qingyan; Li, Yani; Duan, Sifan; You, Ruimin; Huang, Yanni; Li, Zhenhui; et al. (Frontiers in Nutrition, 2024)
Introduction Low skeletal muscle mass and high adipose tissue coexist across the body weight spectrum and independently predict the survival ratio of colorectal cancer (CRC) patients. This combination may lead to a mutually exacerbating vicious cycle. Tumor-associated metabolic conditions primarily affect subcutaneous adipose tissue, but the nature and direction of its relationship with skeletal muscle are unclear. This study aims to examine the bidirectional causal relationship between skeletal muscle index (SMI) and subcutaneous fat index (SFI) during the perioperative period in CRC patients; as well as to validate the association between perioperative SMI, SFI, and CRC prognosis. Methods This population-based retrospective cohort study included patients with stage I-III colorectal cancer who underwent radical resection at the Third Affiliated Hospital of Kunming Medical University between September 2012 and February 2019. Based on inclusion and exclusion criteria, 1,448 patients were analyzed. Preoperative (P1), 2 months postoperative (P2), and 5 months postoperative (P3) CT scans were collected to evaluate the skeletal muscle index (SMI; muscle area at the third lumbar vertebra divided by height squared) and subcutaneous fat index (SFI; subcutaneous fat area at the third lumbar vertebra divided by height squared). A random intercept cross-lagged panel model (RI-CLPM) was used to examine the intra-individual relationship between SMI and SFI, and Cox regression was employed to assess the association between SMI, SFI, recurrence-free survival (RFS), and overall survival (OS). Results The median age at diagnosis was 59.00 years (IQR: 51.00–66.00), and 587 patients (40.54%) were female. RI-CLPM analysis revealed a negative correlation between SFI and subsequent SMI at the individual level: P1-P2 (β = −0.372, p = 0.038) and P2-P3 (β = −0.363, p = 0.001). SMI and SFI showed a negative correlation during P1-P2 (β = −0.363, p = 0.001) but a positive correlation during P2-P3 (β = 0.357, p = 0.006). No significant correlation was found between the random intercepts of SFI and SMI at the between-person level (r = 0.157, p = 0.603). The Cox proportional hazards multivariate regression model identified that patients with elevated SFI had poorer recurrence-free survival (HR, 1.24; 95% CI: 1.00–1.55). Compared to patients with normal preoperative SMI and SFI, those with low SMI or high SFI had poorer recurrence-free survival (HR, 1.26; 95% CI: 1.03–1.55) and overall survival (HR, 1.39; 95% CI: 1.04–1.87). However, no significant association between SMI and SFI and the prognosis of colorectal cancer patients was observed postoperatively. Conclusion In CRC patients, preoperative muscle loss leads to postoperative fat accumulation, exacerbating muscle loss in a feedback loop. Elevated preoperative SFI predicts poorer survival outcomes. Monitoring SMI and SFI is crucial as prognostic indicators, despite non-significant postoperative associations. Further research is needed to improve patient outcomes.